Membaca Tanpa Hambatan: Strategi Literasi untuk Mengatasi Kesulitan Belajar - Hidayat, Hafiz; Ronvy, Al Shaffaat (Jurnal Suloh, 2024)
This study aims to analyze the reading difficulties experienced by second-grade elementary school students and identify effective teaching strategies to help overcome these issues. The subjects of the study include students who struggle with blending syllables, students who do not recognize letters, and students who stutter while spelling. The method used is a case study with a qualitative approach. Data collection techniques include observation, interviews, and document analysis. The results show that the use of phonics methods, syllable-blending exercises, interactive letter recognition, and a gradual approach to spelling successfully improved students' reading skills. However, challenges such as differences in students' abilities and limited instructional time remain obstacles. This study highlights the importance of collaboration between teachers, parents, and students in addressing children's reading difficulties